The Influence of Brand Image and Personal Branding on The Purchase Decision of Menantea Products in the City of Malang, East Java - Nur Rahmah Ningsih; Amelindha Vania (Institute of Computer Science (IOCS), 2022)
This research was conducted to answer the question of how the influence of brand image and personal branding on the purchasing decisions of Menantea products in Malang City, East Java. This research is quantitative by using a survey method. The sampling technique is purposive sampling through questionnaires to 130 respondents for multiple linear regression analysis. Based on the research obtained linear regression equation (Y = 0.249 + 0.505 X1 + 0.294X2 + e) ​​this shows that brand image and personal branding have a positive impact on purchasing decisions. The brand image variable has t count > t table, which is 5,366 > 1,978, then H1 is accepted. So the conclusion is that brand image partially affects purchasing decisions for Menantea products in Malang City. The personal branding variable has t count > t table, which is 3.123 > 1.978, then H2 is accepted. So the conclusion is that personal branding partially affects the decision to purchase Menantea products in Malang City. Based on this research that simultaneously brand image and personal branding have a significant influence on purchasing decisions. The calculated F value is 88.057 > F table 3.07.